O-EGS04 Is group and save necessary for all patients undergoing emergency cholecystectomy: A 6-year retrospective audit. (16th December 2021) - Kuan, Jen Yee; Mohammed, Ahmed; Rajendran, Ilayaraja; Turner, Paul; Ball, Christopher; Date, Ravindra; Krishnamohan, Nitya; Ward, Jeremy; Pursnani, Kishore; Shetty, Vinutha Daya
Abstract: Background: Emergency cholecystectomy (EC) has a low perioperative bleeding risk. There is no current national guideline to suggest routine preoperative Group and Save (G&S) is necessary. Our Trust guideline recommends preoperative G&S for all EC operations. In 2018, a Trust-wide policy was adopted based on an audit, which concluded that routine preoperative G&S is unnecessary for elective cholecystectomy. All G&S require 2samples taken separately, which can delay surgery. The cost to process one sample for G&S is £28. Therefore, a study was set up to assess the need for routine G&S in patients undergoing EC. Methods: This retrospective observational study was based on a prospectively collected hospital database from March 2015 to March 2021 using MS-Excel. All patients who underwent EC (laparoscopic and/or open) within 10 days during index admission were included. All elective cholecystectomies were excluded. Patients were divided into GS-patients (patients with G&S) and NGS-patients (patients without G&S). The primary outcome is the difference between the incidence of 'Perioperative blood transfusion' (PBT) between the studied groups. The overall cost-effectiveness is considered as a secondary outcome. The categorical data were analysed using the Chi-square test; a p-value <0.05 is considered statistically significant. Results: In this 6year period, 2210patients underwent cholecystectomy. Of these, 496patients (22.4%) who underwent EC were included. 447patients (90.1%) were in GS group and 49patients (9.9%) were in the NGS group. None from the NGS group required PBT, whereas 3patients (0.6%) in the GS group received blood transfusion. However, PBT was truly indicated in 1patient due to the associated cardiovascular comorbidities. On the contrary, 2patients did not fit the 'restrictive transfusion threshold' criteria of JPAC. There was no statistically significant difference in PBT requirement between the studied groups (p = 0.331). Deferring routine G&S for EC could have saved our institution £24, 976. Conclusions: Our study has demonstrated that preoperative G&S is not indicated for all emergency cholecystectomies. It takes approximately 1 hour for G&S to be processed unless crossmatching is required. Group O-negative or O-positive blood can be provided to patients when urgent blood transfusion is needed depending on their age and gender. Thus, we conclude that G&S should be restricted to patients with low preoperative haemoglobin, bleeding and clotting disorders, those known to have abnormal blood antibodies and significant cardiovascular comorbidities.